Evaluation of water stress index and water poverty in rice production based on the water footprint concept in Iran - Shahla Dehghanpir; Ommolbanin Bazrafshan; Hadi Ramezani Etedali; Arashk Holisaz; Behnam Ababaei (Mudil/sazī va mudīriyyat-i āb va khāk, 2024)
IntroductionThe increase in water demand, especially in the production of agricultural products, has led to increased competition for fresh water. Therefore, improving agricultural water productivity and reducing water stress caused by agricultural production is an important measure to improve the sustainable use of water resources. One of the most important indicators proposed for water management is the concept of water footprint, which can be used as a useful tool to measure and predict the amount of water consumed in the agricultural sector and the required demand. In addition, water stress and water poverty indicators are among the other widely used indicators to evaluate water scarcity. Iran is an arid and semi-arid country that has faced severe water shortage and this has had adverse effects on the economy, ecosystem functions, and the welfare of the country's people. The agricultural sector is one of the most important and largest consuming sectors of water resources in Iran, so more than 92% of freshwater resources are consumed in this sector, so the knowledge of water resources allocated for the production of agricultural products is important for managers. And the country's policymakers are very important. So, one of the main solutions to reduce water shortage is to reduce water consumption in the agricultural sector. Among agricultural products, rice is one of the most important food products, which feeds more than half of the world's population. Therefore, the purpose of this study is to use the indicators of water footprint, water stress, and water poverty to evaluate the water scarcity of water in rice production in Iran.Materials and MethodsAmong the agricultural products, rice is a valuable food and the most important and widely consumed grain. The study area is the rice-producing provinces. which feeds more than half of the world's population. It accounts for about 19% of the world's dietary energy. After wheat, this product is known as one of the most important food items. The average area under rice cultivation (ha), production (ton), yield (tons/ha) as well as the necessary data and information were collected concerning the water resources available for rice production from the Ministry of Jihad Agriculture and the Water Resources Management Company of Iran. The evaluation of water footprint components, including blue, green, and gray water footprints, is based on the method provided by Hoekstra et al. (2011). The water stress index of rice is calculated as a ratio of the total water footprint in rice production to the total water resources available in the region. The amount of water poverty caused by rice production is defined by the product of the total water footprint in rice production and the value of the rice water stress index. Finally, the amount of export and import of virtual water due to rice production in Iran has been estimated.Results and DiscussionOn average, the total footprint of rice is 3037 m-3 t and the total volume resulting from its production is 4313 MCM, with the share of blue, green, and gray water footprints being 91.68, 6.93, and 1.39 %, respectively. The available water resources (AWR) for rice production in the producing provinces are 21,992 MCM, of which 6,872 and 15,210 MCM are related to blue water and green water, respectively. The results of the investigation of the water stress index (RWSI) caused by rice cultivation in Iran, which is the result of dividing the total water footprint in rice production by the available water resources, is on average equal to 0.5 (out of 1.9), which shows Iran is in moderate water stress of rice production. Changes in water stress in rice production on a provincial scale showed that the provinces of Qazvin, Zanjan, Isfahan, North Khorasan, Razavi Khorasan, and Sistan and Baluchistan have water stress with a value between 0.6 and 1.2 are high and very high water stress in rice production, while the provinces of Mazandaran, Guilan, Golestan, Fars, and Khuzestan are in the range of less than 0.3 (low water stress) Also, the water poverty caused by rice production is equal to 1073 MCM in Iran, which is the highest and lowest amount of water poverty in Guilan and Khuzestan provinces (290 and 11 MCM).ConclusionWater sustainability in rice production in Iran has been investigated using water stress, water poverty, and water footprint, as well as the amount of exports and imports. Among the components of the water footprint, the highest value is related to the blue water footprint, and the lowest is related to the green water footprint. The high blue water footprint shows that most of the surface water and groundwater is used for rice production, and the low green water footprint shows that the amount of rainfall is not enough for rice cultivation in Iran. According to the results, the amount of gray water footprint in rice production is more than the green water footprint, this issue shows that the low yield of rice in the studied provinces as well as the high consumption of fertilizers and chemical pesticides cause the increase of gray water footprint in rice has been produced. Assessing water scarcity using the water footprint approach can be useful for identifying the risks of high rice production due to the potential of water scarcity. The dependence and high consumption of blue water compared to green water have increased the water shortage related to the production of rice. Therefore, it is necessary to change the pattern of water resource allocation based on the status of water resources and water scarcity indicators.